Profit for friends, fairness for strangers: Social distance reverses the endowment effect in proxy decision making. (March 2021) - Kim, Hyunji; Schnall, Simone
Abstract: Buyers often price a product lower than sellers do, a pricing discrepancy known as the endowment effect . We investigated the way buyers and sellers change their pricing decisions as a function of social distance when making decisions on behalf of another person. In Study 1, the pricing discrepancy persisted when making a decision for a close social contact whereas the pattern was reversed when making a decision for a distant social contact. Study 2 replicated this reversed pattern using a social proximity manipulation, and this effect was mediated by participants' prioritizing of fairness over immediate profit of the transaction. The current work suggests that people allocate different value to objects depending on the subjective closeness towards another for whom they make the pricing decision.